A pesquisa em ensino de química como área estratégica para o desenvolvimento da química - Santos, Wildson Luiz Pereira dos (2013)
This paper presents an overview of the development of chemical education as a research area and some of its contributions to society. Although science education is a relatively recent area of research, it went through an expressive development in the last decades. As in the whole world, in Brazil also such development is attested by the expressive number of scientific societies, specialized journals, and meetings with growing attendance in the areas of science education in general and chemical education in particular. Following are the main contributions of research in science education related to chemistry teaching: adoption of teaching-learning principles in chemistry education; contextualization of chemical knowledge; interdisciplinary approach to chemistry teaching; use of the history of science for the definition of contents and for the design of curricula and teaching tools; development of specific disciplines for the initial and in-service training of chemistry teachers; publication of innovative chemistry textbooks by university-based research groups; elaboration of official guidelines for high-school level; and evaluation of chemistry textbooks to be distributed to high-school students by the Brazilian government. In spite of a positive impact of such initiatives, science education in Brazil still faces many problems, as indicated by poor results in international evaluations (such as the Program for International Student Assessment). However, changes in such a scenario depend less on the research in chemical education than on the much-needed governmental initiatives aiming at the improvement of both attractiveness of teaching career and structural conditions of public schools. In conclusion, new government investments in education are necessary for continuing the development of chemistry; moreover, scientific societies and decision makers in educational policies should take into consideration the contributions originated from the chemical education research area.